Uncovering myself to understand you - Lozano Carvajal, Sayra Milena; Velásquez Tangarife, Santiago (Colombian Applied Linguistics Journal, 2017)
Classroom incidents in which teachers have to exhibit their expertise at managing a class is commonplace in teachers’ daily routines, though sometimes some of those classroom incidents turn into critical moments. However, ordinary disruptive classroom situations are not as catastrophic as when teachers themselves provoke them. In addition, when some teachers have to face any sort of classroom disruption, most of them are unable to come up with any immediate and effective solutions. In this paper, we describe how we combined both the critical incident technique and the cooperative development theory so as to reflect upon a critical moment of each of us to be able to improve our viewpoints regarding the potential solutions that can emerge to cope with those critical moments in our own classrooms. The findings show that we strengthened our professional ties, we invigorated our teaching skills, and developed from our own insights into new perspectives in relation to how to better tackle classroom management difficulties. Finally, we share how profound the changes were which, additionally, were not only in the pedagogical sense.